The challenge of flow: state socialist television between revolutionary time and everyday time. (April 2016) - Mihelj, Sabina; Huxtable, Simon
This article contributes to the growing literature on diverse television cultures globally and historically by examining selected aspects of television cultures in the Soviet Union and Yugoslavia. Being part of a political, economic and cultural system that self-consciously set out to develop an alternative form of modern society, state socialist television offers a particularly apposite case study of alternative forms of modern television. State socialist television was inevitably drawn into the Cold War contest between two rival visions of modernity and modern life: one premised on liberal democracy and the market economy, the other on communist rule and the planned economy. As a result, its formats, content and uses were different from those familiar from western television histories. The analysis, based on 70 life-story interviews, schedule analysis and archival sources, focuses on the temporal structures of television and on the challenges posed by television's ability to offer an instantaneous connection to the unfolding present. We argue that the nature of television temporality had ambiguous consequences for the communist project, allowing citizens of state socialist countries to disconnect from communist ideals, while synchronising their daily life with the ongoing march towards the radiant communist future.